(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Through the use of customs accounts the essay analyses the items used and recycled in the late Middle Ages. The two case-studies are the Florentine one, with two Stratti di Gabelle, and the Milanese one through the use of the Liber datii mercantie communis Mediolani:, between the second half of the 14th and the first half of the 15th century. Both rich and populous, and characterised by productions of different kinds and quality, the two cities were among the largest economic and commercial hubs in Italy and Europe. Legislation of a fiscal nature, enacted by the government of the Florentine Republic on the one hand and by the Visconti and later Sforza dukes on the other, placed great emphasis on the taxation of all goods entering and leaving the city gates and their respective territories. The list of merchandises also included second-hand goods, sometimes even cast-offs, as well as recycled and/or to-be-recycled objects. While Milan taxed indifferently all items in circulation, both used and new, applying a duty of 12 denari for every lira of value, Florence, on the other hand, issued specific measures to tax old and worn items differently from new ones, thus envisaging for the second-hand market and for the consumption of those who resorted to it a different economic treatment.